2010
DOI: 10.1007/s11666-010-9571-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceramic Particle Velocity on Cold Spray Deposition of Metal-Ceramic Coatings

Abstract: In this paper, metal-ceramic coatings are cold sprayed taking into account the spray parameters of both metal and ceramic particles. The effect of the ceramic particle velocity on the process of metal-ceramic coating formation and the coating properties is analyzed. Copper and aluminum powders are used as metal components. Two fractions of aluminum oxide and silicon carbide are sprayed in the tests. The ceramic particle velocity is varied by the particle injection into different zones of the gas flow: the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 15 publications
(10 reference statements)
2
35
0
Order By: Relevance
“…This is beneficial to Al adhesion, and the binder effect of soft metal in turn promotes the deposition of SiC, similar to the observation by Shkodkin et al 85 . Grigoriev et al 166 and Sova et al 73,82,83 further pointed out that the addition of ceramics can lower the critical velocity for pure metals, and consequently "critical" temperature (the minimum gas stagnation temperature at which particles begin to adhere) necessary for spraying these metals, and the deposition efficiency also increases at the same time as indicated in Figure 17. 166 A small fraction of ceramic powders (Al2O3, SiC) in the feedstock does produce a strong activation effect on the substrate surface and increases the deposition efficiency of the metal component in the mixture compared to spraying of pure metals.…”
Section: Experimental Workmentioning
confidence: 94%
See 2 more Smart Citations
“…This is beneficial to Al adhesion, and the binder effect of soft metal in turn promotes the deposition of SiC, similar to the observation by Shkodkin et al 85 . Grigoriev et al 166 and Sova et al 73,82,83 further pointed out that the addition of ceramics can lower the critical velocity for pure metals, and consequently "critical" temperature (the minimum gas stagnation temperature at which particles begin to adhere) necessary for spraying these metals, and the deposition efficiency also increases at the same time as indicated in Figure 17. 166 A small fraction of ceramic powders (Al2O3, SiC) in the feedstock does produce a strong activation effect on the substrate surface and increases the deposition efficiency of the metal component in the mixture compared to spraying of pure metals.…”
Section: Experimental Workmentioning
confidence: 94%
“…While a too large fraction of ceramic particles considerably hinders coating deposition because their erosion effect exceeds their activation effect. 73,82 For the activation mechanism of ceramics, Grigoriev et al 166 further identified two mechanisms: (1) ceramic particles increase the substrate roughness, and (2) clean the oxide films from the substrate surface increasing their chemical/metallurgical activity as shown in Figure 18. They also proposed (3) the possible interactive effect of metal and ceramic particles during flight under a very high powder flow rate, which cleans away oxide films on the surface of metal particles and increases chemical/metallurgical activity, though this is not supported by experimental evidence.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are generally two approaches for using cold spray to fabricate metal matrix composite coatings: (a) pretreatment powder processing such as cladding (Ref 12) and sintering (Ref [13][14][15][16][17], and (b) spraying mechanical blends of two or more powders (Ref [18][19][20][21][22][23][24][25]. For mechanically blended ceramic and metallic powders, previous researchers reported co-deposition of metallic particles with oxides and carbides.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that local particle melting must occur at the particlesubstrate interface due to high impact energy. Others suppose that the particle adheres to the substrate additively following the solid-state plastic deformation process, so CS can have expanded opportunities of free form fabrication processes [8,9]. When the accelerated powders are impinged onto the substrate, conversion of their kinetic energy makes it possible for them to proceed with mechanical deformation of the particles, which results in relatively adherent coatings with relatively low porosity.…”
Section: Introductionmentioning
confidence: 99%